2021
DOI: 10.1016/j.adhoc.2020.102403
|View full text |Cite
|
Sign up to set email alerts
|

Trusted and secured D2D-aided communications in 5G networks

Abstract: The design of the forthcoming fifth generation (5G) system shall meet the severe requirement of managing an always increasing amount of traffic generated by both humans and machines, while guaranteeing data security. Among the enabling technologies that will turn 5G into a reality, Device-to-Device (D2D) and Multicasting will certainly play a key role because of their capability to largely improve network resources utilization and to address emerging use cases requiring the delivery of the same content to a la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 33 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…shows, D 1 has jurisdiction to take the encryption of message Msg using the shared private key. Thus D 1 has jurisdiction over message Msg and vice versa, D 2 also has jurisdiction to use a shared private key and thus D 2 has jurisdiction over message Msg also shown in Equation(10).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…shows, D 1 has jurisdiction to take the encryption of message Msg using the shared private key. Thus D 1 has jurisdiction over message Msg and vice versa, D 2 also has jurisdiction to use a shared private key and thus D 2 has jurisdiction over message Msg also shown in Equation(10).…”
mentioning
confidence: 97%
“…However, typical D2D communication in LTE-A/5G, when allowed to work as intelligent forwarding agent relays, consequently, exposed the communication to several security vulnerabilities and breaches, for instance, quantum attacks, 51% attacks [3], man in the middle (MITM) attack, masquerading attack, denial of service (DoS) attack, rouge relay attack and privacy issues in current 5G/6G cellular networks. Several security schemes have been proposed for D2D communication security which includes River Shamir Adleman (RSA) [4], Diffie Hellman (DH) [5], Elliptic Curve Cryptography (ECC) [6]- [8] , Elliptic Curve Cryptography with Diffie Hellman (ECDH) [9], [10] are few combinations that have been used. These security challenges are more crucial and harder to mitigate because of the resourceconstrained nature of cellular devices.…”
mentioning
confidence: 99%
“…Sidelink technology, which is an extension of the LTE system allowing for D2D communications without using BS as an intermediate point, can be utilized to bridge over the multicast difficulties [198], [199]. For example, in such a system, sidelinks may provide service to UEs experiencing degraded Sidelink assistance [122] Energy reduction Heuristic algorithms for multicast data delivery [123] Optimal multicast scheduling Group partition and beam selection algorithm [124] Optimal user partitioning Multicast scheduling algorithm [125] Power consumption/interference minimization Relay selection and power allocation algorithm [126] Latency, reliability, data rate, and spectral efficiency Location-based hybrid multiple access scheme [127] Secure data delivery Approach for assessment of relay trustworthiness [128] Sidelink transmission security Reliable management of multicast services in a 5G IoT [129] System capacity maximization Spectrum sharing and caching selection strategy RIS assistance [130] Power control, QoS, fairness RIS optimization algorithm [131] Downlink power control Passive beamforming scheme [132] Energy efficiency maximization RIS-based resource allocation methods [133] Choice of the optimal reflection coefficients Analytical method for RIS configuration [134] Secure RIS beamforming Analytical optimization via semidefinite relaxation [135] Maximization of RIS secrecy rate Analytical assessment via stochastic geometry [136] Channel capacity maximization Optimization via gradient descent method [137] Simultaneously transmitting and reflecting RISs Overview of state-of-the-art algorithms [138] RIS-assisted multicasting modeling Analytical model via queuing theory NTN assistance [139] Radio resource sharing Resource allocation cooperative T-NTN algorithm [140] Simultaneous usage of NTN/terrestrial systems Cooperative multicast/unicast transmission scheme [141] Spectral efficiency maximization Radio resource management scheme [142] Capacity and spectral efficiency maximization Dynamic beam area formation algorithm [143]- [146] Exhaustive coverage of NTN usage in 5G/6G Survey covering NTN-aided multicasting MEC assistance…”
Section: A Sidelink-assisted Multicastingmentioning
confidence: 99%
“…While it has been demonstrated that sidelink communications can enhance point-to-multipoint transmissions through efficient relay selection, direct D2D connections present even greater security challenges since data exchange occurs directly between nodes in close proximity. In [127], a to effectively deliver trustworthy multicast/broadcast traffic in 5G-oriented networks is introduced to address this issue. In the same vein, a protocol for effectively managing multicast services with a particular emphasis on security in a 5Goriented IoT environment is proposed in [128].…”
Section: A Sidelink-assisted Multicastingmentioning
confidence: 99%
“…This was done by obstructing the eavesdropping device. Different security models and algorithms were designed to measure the security workload on heterogeneous mobile devices [169]- [171]. Besides that, an in-depth survey on security design aims was introduced in [126], [157], [172].…”
Section: E Securitymentioning
confidence: 99%